Pertanggungjawaban Pelaku Tindak Pidana Pembuatan Dan Pemalsuan Surat Keterangan Catatan Kepolisian (SKCK) Sebagai Syarat Daftar Pekerjaan Di PT. GGP Humas Jaya - Gracemark Chrissaulita Panjaitan; Lukmanul Hakim; Ansori Ansori (JUSTICIA SAINS - Jurnal Ilmu Hukum, 2023)
The criminal act of counterfeiting is a form of crime that is quite widely committed by the community with or without a tool, because in today's modern era, technological advances are increasingly rapid which can support criminals so that it is easier to commit a crime of forgery or fraud. A person is said to have committed a criminal act, if his act is proven to be a criminal act as stipulated in the applicable criminal laws and regulations. However, someone who has been proven to have committed a criminal act cannot always be sentenced to a crime. This is because in criminal liability, it is not only seen from the actions, but also seen from the element of guilt. Criminal liability is a legal mechanism in which every person who commits a crime or violates the law, as defined in the law, must be held accountable for his actions according to his mistakes. The term criminal law has a plural meaning. In criminal law the concept of responsibility is a central concept known as the teaching of error. Certificate of Police Records (SKCK) is a letter or record evidence from the Police Agency through Security Intelligence units (Intelkam) regarding a person's track record or history in the criminal field which explains whether or not a person has committed a crime.